What Makes the Maine State Library Unique? - Lord, Linda (Maine Policy Review, 2013)
Linda Lord describes the Maine State Library and its unique role in the state.The MSL’s service model requires it to provide services to other libraries in the state; to deliver and provide resources to the citizens of the state; to serve other state agencies; and to be a conduit with federal agencies and the Maine State Legislature.
Keywords: Maine; state library